2022
DOI: 10.1111/jvim.16589
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sex on renin‐angiotensin‐aldosterone system metabolites and enzymes in Doberman Pinschers

Abstract: Background: Estrogen modulates the renin-angiotensin-aldosterone system (RAAS) in women, but sex differences have not been fully explored in dogs.Objective: We hypothesized that the RAAS profile of intact female (IF) Doberman Pinschers (DP) would differ from spayed female (SF) and intact male (IM) DP.Animals: Eighteen healthy DP (6 IF, 6 SF, 6 IM).Methods: Absolute and indexed RAAS metabolites, angiotensin-converting enzyme (ACE) and ACE2 activities, and genotypes (pyruvate kinase dehydrogenase 4, titin, and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
1
2
1
Order By: Relevance
“…Consistent with previous studies of the known ACE variant in dogs, we found that ACE activity was significantly lower in ACE gene variant positive dogs compared to ACE gene wildtype dogs 31 . The lack of difference in ACE-S (a proposed surrogate for ACE activity) between ACE variant and wildtype dogs has also been previously reported 32 , 33 . Because ACE-S is simply the ratio of angiotensin II to angiotensin I, it appears not to reflect true ACE activity in dogs with the ACE variant because other non-ACE enzymes (e.g.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Consistent with previous studies of the known ACE variant in dogs, we found that ACE activity was significantly lower in ACE gene variant positive dogs compared to ACE gene wildtype dogs 31 . The lack of difference in ACE-S (a proposed surrogate for ACE activity) between ACE variant and wildtype dogs has also been previously reported 32 , 33 . Because ACE-S is simply the ratio of angiotensin II to angiotensin I, it appears not to reflect true ACE activity in dogs with the ACE variant because other non-ACE enzymes (e.g.…”
Section: Discussionsupporting
confidence: 59%
“…The activity of ACE2 has not been previous reported in dogs with CHF. The ACE2 activity for this group of CHF dogs was notably higher than reported for both healthy people and people with CHF 34 but was not markedly different from healthy dogs 33 . This enzyme is a marker for disease severity in people with heart disease.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations